Investigating kinematic of the flip turn technique in front crawl swimming - Bahadoran, M.; Mosavi, S. H.; Hasannejad, E.; Moradlo, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to biomechanically describe the tumble turn kinematics variables in front crawl. Ten experienced swimmers were recruited in this study. During freestyle tumble turns, selected kinematic variables were recorded. Kinematics weres calculated using underwater videography. Correlation s between these variables showed that there were good relations between speed-in and wall contact time, time-in and speed-in, time-out and speed out, time in and wall contact time, speed out and wall contact, time-out and wall contact time, time-out and time streamlining, and wall contact time and time streamlining. However an optimal combination of reduced streamlining time and increased wall contact time are conducive to improve performance.